(untitled) (CIPEEX, 2022)
THIS WORK WAS PRESENTED DURING THE IX CULTURAL EXHIBITION OF THE DENTISTRY COURSE IN THE FORMAT OF A PHOTOGRAPHIC EXHIBITION. FAKE NEWS OR FAKE NEWS HAS BECOME POPULAR THROUGH SOCIAL NETWORKS. IT IS CHARACTERIZED AS FAKE NEWS, BUT IT IS WRITTEN TO CONVINCE ITS READERS THAT A FACT OR AN EVENT IS REAL. THIS NEWS HAS A GREAT POWER OF DISSEMINATION, THAT IS, THEY GO VIRAL ON SOCIAL NETWORKS REACHING A LARGE NUMBER OF READERS, AND THE GREATER THIS NUMBER, THE GREATER THE IMPRESSION THAT THEY SEEM MORE AND MORE TRUE AND LEGITIMATE. MANY PEOPLE BELIEVE THAT THE NEWS IS TRUE, EITHER BY THE SOURCE THEY RECEIVED OR BY THE SUBJECT, AND INCREASINGLY SHARE WITHOUT CHECKING THE ORIGIN OR VERACITY, REACHING THE OBJECTIVE FOR WHICH THE FAKE NEWS WAS CREATED. FAKE NEWS BECAME POPULAR DURING THE NORTH AMERICAN ELECTIONS IN 2016 AND ITS TARGET AUDIENCE IS PEOPLE WITH A LOWER LEVEL OF EDUCATION WHO END UP CHOOSING SOCIAL NETWORKS AS A SOURCE OF INFORMATION. IT IS ALWAYS GOOD TO POINT OUT THAT THE STRATEGY IS TO DECEIVE THE READER. IT CAN BE COMPARED TO GOSSIP, BUT WITH THE IMMENSE POWER OF DISSEMINATION.